REAKSI INVESTOR DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN-PERUSHAAN DI BURSA EFEK JAKARTA - Murniningsih, Rochitati (Jurnal Analisis Bisnis Ekonomi, 2007)
Company responbility not only limited to just creditor and investor but also have to hold responsible to employees, consumer and environmental about. Through social expression, company can communicate the social activity and also obtain the legitimasi from all stakeholder. Expression of social Responbility presented by a company will give the influence for investor in decision making its investment. This research aim to test empirically social responbility expression influence of comapny to investor reaction. This research population is company enlisted in BEJ in the year 2005. Technique on Intake sampel use the method of purposive sampling. Obtained sample as much 52 company that is 40 incoming company categorize the high profile and 12 incoming company categorize the low profile. Result of examination in this research have fulfilled the classic assumption that is do not find of multikolinearitas, autokorelasi and heterokedastisitas. Result of test of normalitas data indicate that the normal distribution data. Result of test F indicate that by simultan all free variable (ownersip of management, size, profile, leverage and profitability) having an effect on significant to investor reaction. Result of test t indicate that by parsial variable of ownership and profile have an effect on the significant to investor reaction.